Cuantificación de compuestos fenólicos de las almendras de cacao para su aplicación y evaluación antimicrobiana en leche cruda. - Villegas Vélez, Leyner Alexander (My University, 2024)
Phenolic compounds are a broad class of secondary metabolites from plants and fruits, being well known for their antioxidant and antimicrobial properties; within health with also known as anti-inflammatory and anti-cancer; playing a crucial role in defending plants against environmental stress. Cocoa beans, especially the Creole, Nacional and CCN-51 varieties, are very rich in phenolic compounds, which makes them a very important object of study, obviously depending on the variety and the processing method. The purpose of this research project focuses on the content of total polyphenols to be applied and evaluated as a natural preservative in processed or untreated foods. The treatments carried out on the cocoa beans were prepared in 4 samples (M1, M2, M3, M4) and dissolved in ethanolic solutions in water in different ratios: Sterile water, ethane-water 50:50, ethanol-water 70:30, 100% ethanol respectively. Lyophilization allowed the polyphenols to be extracted in higher concentrations, to subsequently be quantified at a p-value=5.08E-11, with significant differences between the samples M1=2.667±0.13mg/g sample, M2=7.718±0.14 mg/g/g sample. g sample, M3=10.996±0.04 mg/g sample and M4=16.482±6.53E-5 mg/g; In the same way, for the content of reducing sugars, where there were significant differences with p-value=9.30E-9, with values obtained in M1=10.830±0.16mg/g sample, M2=7.411±0.13 mg/g sample, M3=4.257±0.16 mg/g sample and M4=2.799±4.93E-4 mg/g sample. The determination of the antioxidant capacity obtained from the polyphenolic extracts also showed significant differences with a p-value=2.49E-8, with results in M1=1.325±8.67E-4mg/g sample, M2=2.140±1.89E-3mg/ g sample, M3=3.031±4.47E-3mg/g sample and M4=4.432±0.07 mg/g sample. The analyzes carried out by CLAE in samples M1 and M4 were able to identify phenolic compounds in both samples, such as catechins with RT=0.63 min, m/z=296.16 mg and 9.08 ppm; theobromine with RT=8.05 min, m/z=181.07 mg and 10ppm; gallic acid with RT=3.63 min, m/z=165.14 mg and 13.03ppm; Vanillic acid RT=14.33 min, m/z=171.02 mg and 11.34ppm; Resveratrol with RT=17.01 min, m/z=168.01 mg and 10.89ppm, among others; fulfilling antimicrobial inhibition functions in raw milk. The microbiological analysis allowed the evaluation of raw milk, applying phenolic compounds in different concentrations: C1=3%, C2=5% and C3=7%, with high antioxidant capacity and inhibitory effect on microorganisms, notably observing the decrease in antimicrobial activity due to the use of polyphenols as a natural preservative in foods without treatment, allowing the predominant microorganisms to be reduced. In the colony count, a control of raw milk microorganisms was carried out without the presence of phenols with 510 CFU, and other samples evaluated with the presence of phenols in microorganisms predominant in E. Coli: C1=91 CFU, C2=65 CFU and C3=42 CFU with effect inhibitor in C1=82%, C2=87% and C3=92%; mesophilic aerobes: C1=75CFU, C2=63CFU and C3=45CFU with inhibitory effect on C1=85%, C2=88% and C3=91%, and molds and yeasts: C1=240CFU, C2=192CFU and C3=136CFU with inhibitory effect on C1=53%, C2=62% and C3=73%.
Los compuestos fenólicos son una amplia clase de metabolitos secundarios de las plantas y frutas, siendo muy conocidos por sus propiedad antioxidantes y antimicrobianas; dentro de la salud con conocidas también como desinflamatorios y anticancerígenos; desempeñando un papel crucial en la defensa de las plantas contra el estrés ambiental. Las almendras de cacao en especial las variedades criollas, nacional y CCN-51 son muy ricas en compuestos fenólicos, lo que las convierte en un objeto de estudio muy importante, obviamente dependiendo de variedad y el método de procesamiento. La finalidad de este proyecto de investigación se centra en el contenido de polifenoles totales para ser aplicados y evaluados como conservante natural en alimentos procesados o sin tratamiento. Los tratamientos realizados a las almendras de cacao fueron preparados en 4 muestras (M1, M2, M3, M4) y disueltas en soluciones etanólicas en agua en diferentes relaciones: Agua estéril, etano-agua 50:50, etanol-agua 70:30, etanol 100% respectivamente. La liofilización permitió que los polifenoles sean extraídos en mayores concentraciones, para posteriormente ser cuantificados a un p-valúe=5.08E-11, existiendo diferencias significativas entre las muestras M1=2.667±0.13mg/g muestra, M2=7.718±0.14 mg/g muestra, M3=10.996±0.04 mg/g muestra y M4=16.482±6.53E-5 mg/g; de la misma forma, para el contenido de azucares reductores, donde hubo diferencias significativas con p-valúe=9.30E-9, con valores obtenidos en M1=10.830±0.16mg/g muestra, M2=7.411±0.13 mg/g muestra, M3=4.257±0.16 mg/g muestra y M4=2.799±4.93E-4 mg/g muestra. La determinación de la capacidad antioxidante obtenidos de los extractos polifenólicas también existieron diferencias significativas con un p-valúe=2.49E-8, con resultados en M1=1.325±8.67E-4mg/g muestra, M2=2.140±1.89E-3mg/g muestra, M3=3.031±4.47E-3mg/g muestra y M4=4.432±0.07 mg/g muestra. Los análisis realizados por CLAE en las muestras M1 Y M4 se logró identificar compuestos fenólicos en ambas muestras, tales como catequinas con RT=0.63 min, m/z=296.16 mg y 9.08ppm; teobromina con RT=8.05 min, m/z=181.07 mg y 10ppm; ácido gálico con RT=3.63 min, m/z=165.14 mg y 13.03ppm; ácido Vanílico RT=14.33 min, m/z=171.02 mg y 11.34ppm; Resveratrol con RT=17.01 min, m/z=168.01 mg y 10.89ppm, entre otras; cumpliendo funciones de inhibición antimicrobiana en la leche cruda. El análisis microbiológico permitió evaluar la leche cruda, aplicando compuestos fenólicos en diferentes concentraciones: C1=3%, C2=5% y C3=7%, con alta capacidad antioxidante y efecto inhibidor de microorganismos, observando notoriamente la disminución de la actividad antimicrobiana por el uso de los polifenoles como conservante natural en alimentos sin tratamiento, permitiendo reducir los microorganismos predominantes.En el recuento de colonias, se realizó un control de microorganismos leche cruda sin presencia de fenoles con 510UFC, y otras muestras evaluadas con presencia de fenoles en microorganismos predominantes en E. Coli: C1=91UFC, C2=65UFC y C3=42UFC con efecto inhibidor en C1=82%, C2=87% y C3=92%; aerobios mesófilos: C1=75UFC, C2=63UFC y C3=45UFC con efecto inhibidor en C1=85%, C2=88% y C3=91%, y mohos y levaduras: C1=240UFC, C2=192UFC y C3=136UFC con efecto inhibidor en C1=53%, C2=62% y C3=73%.
Keywords: COMPUESTOS FENOLICOS; FOLIN CIOCALTEU; DNS; POLIFENOLES